Photographie et écologie aux États-Unis: l’image à contre-emploi - François Brunet (Transatlantica)
A traditional and powerful connection links landscape art and environmental consciousness in North American art, classically embodied in artists such as Thomas Cole in painting and Ansel Adams in photography, and reinforced since the 1970s by various photographic projects animated with militant environmentalist purposes. This article seeks to assess the role(s) that photographs, in and of themselves, have played in these artistic-militant enterprises; and to contrast them with the role of discourses (of artists, historians, critics, and so on) in setting forth political contents or intentions that the works themselves have reflected only ambiguously or even, sometimes, flatly contradicted. This contribution proposes a short history of this question through three successive stages: a) the creation of Yellowstone National Park (1872), which, according to a persistent historiographical legend, allegedly resulted from the timely distribution to Congress members of pictures by survey photographer William H. Jackson; b) the work and career of Ansel Adams, envisioned as the paradox of a highly polished style of landscape photography whose classic, mainstream look tended to contradict its underlying conservationist message; c) a series of more recent books and exhibitions (1975-2010), bringing together artistic projects that highlighted deconstructions of classic, iconic landscapes, or examples of the degradation and destruction of natural sites, while maintaining a stylistic taste for spectacular effect and spotless finish that seemed to contradict the artists’ avowed message.